A study to evaluate feto-maternal outcome of trial of labour in previous cesarean patients: a prospective observational study at a tertiary care centre in India - Tambe, Sanjaykumar G.; Mulay, Ameya S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Vaginal birth after cesarean section (VBAC) is associated with shorter maternal hospitalizations, less blood loss and fewer transfusions, and fewer thrombo-embolic events than cesarean section (C-section). A 60 to 70% success rate of vaginal birth after previous C-section has been reported by many authors if the primary cesarean was done for nonrecurring indications the subsequent pregnancy Methods: A prospective observational study was conducted at Sassoon general hospital, Pune, India. The 100 patients who fulfilled the inclusion criteria were studied. Maternal and fetal outcomes were analysed. Results: Out of the total 100 cases with previous C-section, successful vaginal delivery was possible in 65% cases. Most common reason for failed attempt to vaginal delivery was failure of labour to progress (40%) followed by failure of induction (28.6%) and non-reassuring FHR (22.9%). Out of the total 35 cases with gestation age over 40 weeks, 51.4% underwent C-section delivery as compared to 26.2% with gestation age of less than 40 weeks (p<0.01). Scar rupture was observed in only a single case out of 65 vaginal deliveries (1.5%). Conclusions: Our study demonstrates that the attempt at the trial of vaginal delivery following a previous C-section, has an good success rate. The risk of unsuccessful attempt is increased by body mass index (BMI) >25, gestation ≥40 weeks and history of previous emergency CS while high success rate was seen with history of any vaginal deliveries. We thus recommend that pregnant woman with history of C-section should be given the option of trial of labour after caesarean (TOLAC), unless contraindicated.